Effect of Lower Blood Pressure Goals on Left Ventricular Structure and Function in Patients With Subclinical Hypertensive Heart Disease. (5th July 2020) - Levy, Phillip D; Burla, Michael J; Twiner, Michael J; Marinica, Alexander L; Mahn, James J; Reed, Brian; Brody, Aaron; Ehrman, Robert; Brodsky, Allie; Zhang, Yiying; Nasser, Samar A; Flack, John M
Abstract: BACKGROUND: Subclinical hypertensive heart disease (SHHD) is a precursor to heart failure. Blood pressure (BP) reduction is an important component of secondary disease prevention in patients with SHHD. Treating patients with SHHD utilizing a more intensive BP target (120/80 mm Hg), may lead to improved cardiac function but there has been limited study of this, particularly in African Americans (AAs). METHODS: We conducted a single center, randomized controlled trial where subjects with uncontrolled, asymptomatic hypertension, and SHHD not managed by a primary care physician were randomized to standard (<140/90 mm Hg) or intensive (<120/80 mm Hg) BP therapy groups with quarterly follow-up for 12 months. The primary outcome was the differences of BP reduction between these 2 groups and the secondary outcome was the improvement in echocardiographic measures at 12 months. RESULTS: Patients (95% AAs, 65% male, mean age 49.4) were randomized to the standard ( n = 65) or the intensive ( n = 58) BP therapy groups. Despite significant reductions in systolic BP (sBP) from baseline (−10.9 vs. −19.1 mm Hg, respectively) ( P < 0.05), no significant differences were noted between intention-to-treat groups ( P = 0.33) or the proportion with resolution of SHHD ( P = 0.31). However, on post hoc analysis, achievement of a sBP <130 mm Hg was associated with significant reduction in indexed left ventricular mass (−6.91 gm/m 2.7 ; P = 0.008) which remained significant on mixed effect modeling ( P = 0.031). CONCLUSIONS: In post hoc analysis, sBP <130 mm Hg in predominantly AA patients with SHHD was associated with improved cardiac function and reverse remodeling and may help to explain preventative effects of lower BP goals. CLINICAL TRIALS REGISTRATION: Trial Number NCT00689819.